Agências de notícias na Internet como serviços de informação para negócios - Natalia Guine de Mello Carvalho (2001)
This work aims to highlight the business information service potential existing in services available at News Agencies websites. Five major national agencies with websites were selected, and four main information services were selected to be analyzed under the information quality and value added perspectives. The perception of the use of these services was obtained from three types of users, to complete this analysis, according to the recommendations found in the literature used as the background for this work.